Methylisoindigo preferentially kills cancer stem cells by interfering cell metabolism via inhibition of LKB1 and activation of AMPK in PDACs - Cheng, Xinlai; Kim, Jee Young; Ghafoory, Shahrouz; Duvaci, Tijen; Rafiee, Roya; Theobald, Jannick; Alborzinia, Hamed; Holenya, Pavlo; Fredebohm, Johannes; Merz, Karl-Heinz; Mehrabi, Arianeb; Hafezi, Mohammadreza; et al. (Molecular oncology, 2016)
Pancreatic ductal adenocarcinoma (PDAC) clinically has a very poor prognosis. No small molecule is available to reliably achieve cures. Meisoindigo is chemically related to the natural product indirubin and showed substantial efficiency in clinical chemotherapy for CML in China. However, its effect on PDAC is still unknown. Our results showed strong anti-proliferation effect of meisoindigo on gemcitabine-resistant PDACs. Using a recently established primary PDAC cell line, called Jopaca-1 with a larger CSCs population as model, we observed a reduction of CD133+ and ESA+/CD44+/CD24+ populations upon treatment and concomitantly a decreased expression of CSC-associated genes, and reduced cellular mobility and sphere formation. Investigating basic cellular metabolic responses, we detected lower oxygen consumption and glucose uptake, while intracellular ROS levels increased. This was effectively neutralized by the addition of antioxidants, indicating an essential role of the cellular redox balance. Further analysis on energy metabolism related signaling revealed that meisoindigo inhibited LKB1, but activated AMPK. Both of them were involved in cellular apoptosis. Additional in situ hybridization in tissue sections of PDAC patients reproducibly demonstrated co-expression and -localization of LKB1 and CD133 in malignant areas. Finally, we detected that CD133+/CD44+ were more vulnerable to meisoindigo, which could be mimicked by LKB1 siRNAs. Our results provide the first evidence, to our knowledge, that LKB1 sustains the CSC population in PDACs and demonstrate a clear benefit of meisoindigo in treatment of gemcitabine-resistant cells. This novel mechanism may provide a promising new treatment option for PDAC.